The relationship between dietary inflammatory index and all-cause and cardiovascular disease-related mortality in adults with metabolic syndrome: a cohort study of NHANES - Ma, Qunwei; Zhang, Ying; Zhang, Daowen; Liu, Cancan; Zhu, Weiwei; Wang, Guixia; Xu, Nannan; Zhang, Xue; Huang, Rui; Zhang, Huijun; Xu, Shuhang; Liu, Chao; et al. (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the correlation between dietary inflammatory index (DII) and mortality resulting from all-cause and cardiovascular diseases (CVD) in adults affected by metabolic syndrome (MetS).MethodsThe focus of this study was to analyze the information of 13,751 adults who had been diagnosed with MetS. DII scores were computed based on a 24-hour dietary intake at the start of the study. By implementing both the Cox regression analysis and restricted cubic spline(RCS) analysis, we examined the correlation between DII score and mortality.ResultsAfter a mean follow-up duration of 114 months, a total of 2,343 individuals (representing 13.45% of the sample) died, with 639 fatalities attributed to CVD. The degrees of dietary inflammation were classified into three groups based on DII scores: low, medium, and high-grade. The mortality rates for each tertile of DII were 11.55%, 13.96%, and 15.05%, respectively. In comparison to participants with T1, the multivariate-adjusted hazard ratios (HR) and 95% confidence intervals (CI) for participants with T3 were 1.16 (95% CI: 1.01-1.34) regarding mortality caused by any reason, and 1.26 (95% CI: 0.95-1.68) for mortality related to CVD. Through the use of the Kaplan-Meier survival curve and RCS, it was observed that individuals in the high DII tertile had an increased likelihood of death compared to those in the low DII tertile.ConclusionOur findings provide validation of the theory that diets high in inflammatory substances contribute to elevated mortality rates for all causes and CVD-related deaths in individuals diagnosed with MetS.